Netnographic Analysis of Youtube Users Comments on Conservation Threats - Sheidy Yudhiasta; Leily Suci Rahmatin (Jurnal Spektrum Komunikasi, 2022)
Conservation and mining are considered as two contradictory aspects of an activity. Conservation activities will be lost if mining development does not match the area analysis. Ecosystems are threatened, and endemic species in an area will become extinct. Mining activities are often two sharp blades. On the one hand, it will increase the economy. However, on the other hand, the more significant damage will make it difficult for the ecosystem to return to its original condition. This is what is currently happening in the Sangihe Islands. Gold mining has become an issue in online discussions on the internet; objections and protests are conveyed to preserve the ecosystem of the region, not only from endemic animal and plant species but also from human existence. This research was conducted by exploring public comments, especially YouTube users in the comments column of the BBC News Indonesia YouTube video: Tambang Emas Pulau Sangihe Mengancam Hutan dan Burung Endemik yang Hampir Punah. A qualitative approach is used in this study with netnographic analysis to analyze netizen comments on BBC News Indonesia YouTube videos. Data retrieval using the botster.io website and analyzed using NVivo 12 software as a qualitative research management tool. The data obtained is 1.000 comments in the comments column. The analysis results show that the majority of internet residents in comments on YouTube videos uploaded by BBC News Indonesia gave a negative response to the Sangihe Island gold mine because it was considered a threat to the conservation and extinction of Sangihe's endemic species, namely the Sangihe Seriwang bird. People on the internet also respond that policy makers' participation in making regulations is important to cancel decisions related to the mining area.